Role of CD1d- and MR1-Restricted T Cells in Asthma - Iwamura, Chiaki; Nakayama, Toshinori (Frontiers in Immunology, 2018)
Innate T lymphocytes are a group of relatively recently identified T cells that are not involved in either innate or adaptive immunity. Unlike conventional T cells, most innate T lymphocytes express invariant T cell receptor to recognize exogenous non-peptide antigens presented by a family of non-polymorphic MHC class I-related molecules, such as CD1d and MHC-related molecule-1 (MR1). Invariant natural killer T (iNKT) cells and mucosal-associated invariant T (MAIT) cells quickly respond to the antigens bound to CD1d and MR1 molecules, respectively, and immediately exert effector functions by secreting various cytokines and granules. This review describes the detrimental and beneficial roles of iNKT cells in animal models of asthma and in human asthmatic patients and also addresses the mechanisms through which iNKT cells are activated by environmental or extracellular factors. We also discuss the potential for therapeutic interventions of asthma by specific antibodies against NKT cells. Furthermore, we summarize the recent reports on the role of MAIT cells in allergic diseases.